Prognostic significance of the lymphocyte-to-monocyte ratio in patients with malignant pleural mesothelioma. Issue 1 (October 2015) - Yamagishi, Tomoko; Fujimoto, Nobukazu; Nishi, Hideyuki; Miyamoto, Yosuke; Hara, Naofumi; Asano, Michiko; Fuchimoto, Yasuko; Wada, Sae; Kitamura, Kenichi; Ozaki, Shinji; Kishimoto, Takumi
Highlights The LMR is an independent marker of prognosis in patients with malignant pleural mesothelioma. The LMR is superior to the other inflammation-based marker regarding prognostic ability. The LMR is a simple marker and is feasible to predict patient's outcome in routine clinical practice.